2007
DOI: 10.1103/physrevd.75.064020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of linear perturbations inf(R)gravity

Abstract: We consider predictions for structure formation from modifications to general relativity in which the Einstein-Hilbert action is replaced by a general function of the Ricci scalar. We work without fixing a gauge, as well as in explicit popular coordinate choices, appropriate for the modification of existing cosmological code. We present the framework in a comprehensive and practical form that can be directly compared to standard perturbation analyses. By considering the full evolution equations, we resolve per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
404
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(410 citation statements)
references
References 49 publications
6
404
0
Order By: Relevance
“…Let us though note that its presence stems from the new effective matter sources peculiar to the particular class of modified gravity models. It has been recently found that such a scale-dependent term is absent in various modified gravity theories within the metric formalism [39,40,41,42].…”
Section: Cosmology With Generalized Dark Mattermentioning
confidence: 99%
“…Let us though note that its presence stems from the new effective matter sources peculiar to the particular class of modified gravity models. It has been recently found that such a scale-dependent term is absent in various modified gravity theories within the metric formalism [39,40,41,42].…”
Section: Cosmology With Generalized Dark Mattermentioning
confidence: 99%
“…First, we would like to narrow the parameter choices to yield expansion histories that are observationally viable, i.e. that deviate from ΛCDM in the effective equation of state (15) by no more than |1+ w eff | 0.2 during the acceleration epoch. This equates to choosing a value for the field at the present epoch…”
Section: Expansion Historymentioning
confidence: 99%
“…The addition of a non-linear function of the Ricci scalar R to the Einstein-Hilbert action has been demonstrated to cause acceleration for a wide variety of f (R) functions [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,…”
Section: Introductionmentioning
confidence: 99%
“…This requirement is twofold: at the background level, the predicted expansion history has to be coherent with distance measurements such as those from Supernovae (SNe), the position of the CMB peaks, and baryon acoustic oscillations (BAO); on the other hand, the modified predictions for structure formation need to pass the test of comparison with the observed large scale structure (LSS) of the Universe. It has been shown for several cases -for instance for f (R) [14][15][16][17][18] and DGP [19][20][21][22][23][24] -that the structure formation test can dramatically reduce the parameter space left unconstrained from the background test, and it is therefore instrumental to the quest for a truly viable model.…”
Section: Introductionmentioning
confidence: 99%